Modernization and westernisation of the Japanese traditional culture as prerequisites of globalization (International relations and international law Journal, 2016)
The article discussed the characteristics of the process of westernization and modernization of Japanese culture. It is also said about how this process took place and people’s reaction to such changes. In general, described the results of effects of these processes on Japanese culture.
Keywords: cultural modernization and westernisation